Amino acid derivative reactivity assay–organic solvent reaction system: A novel alternative test for skin sensitization capable of assessing highly hydrophobic substances. Issue 10 (26th February 2021) - Yamaga, Hiroaki; Watanabe, Shinichi; Fujita, Masaharu; Yamamoto, Yusuke; Kasahara, Toshihiko; Kataoka, Shinsuke
Abstract: The amino acid derivative reactivity assay (ADRA) is an in chemico alternative to animal testing that focuses on protein binding. The ADRA is a skin sensitization test that solves problems associated with the direct peptide reactivity assay. However, when utilizing the ADRA to evaluate highly hydrophobic substances with octanol/water partition coefficients (logKow) of >6, the test substances may not dissolve in the reaction solution, which can prevent the accurate assessment of skin sensitization. Therefore, we developed the ADRA–organic solvent (ADRA‐OS) reaction system, which is a novel skin sensitization test that enables the assessment of highly hydrophobic substances with a logKow of >6. We discovered that the organic solvent ratio, the triethylamine concentration, and the ethylenediaminetetraacetic acid disodium salt dihydrate concentration participate in reactions with the nucleophile N ‐(2‐(1‐naphthyl)acetyl)‐l ‐cysteine (NAC) and sensitizers that are used in ADRA and in stabilizing NAC. Thus, we determined the optimal reaction composition of the ADRA‐OS according to L9 (3 3 ) orthogonal array experiments. Using this test, we assessed 14 types of highly hydrophobic substances. When we compared the results with ADRA, we found that ADRA‐OS reaction system has high solubility for highly hydrophobic substances and that it has a high predictive capacity (sensitivity: 63%, specificity: 100%, accuracy: 79%). The implication of the results is that the novel ADRA‐OS reaction system should provide a useful method for assessing the skin sensitization of highly hydrophobic substances with a logKow of >6. Abstract : We developed the ADRA‐OS reaction system, a novel method for assessing hydrophobic substances (which have traditionally presented challenges in ADRA), as an in chemico alternative to animal testing for skin sensitization. The novel test was used to assess 14 types of highly hydrophobic substances with a logKow of >6. Compared with the ADRA, the ADRA‐OS reaction system showed increased solubility of highly hydrophobic substances and high predictive performance (sensitivity: 63%, specificity: 100%, and accuracy: 79%).